Attachment limited versus diffusion limited nucleation of organic molecules: Hexaphenyl on sputter-modified mica - Tumbek, L. (North-Holland Pub. Co, 2012)
The nucleation and growth of organic molecules is usually discussed in the framework of diffusion limited aggregation (DLA). In this letter we demonstrate for the rod-like organic molecules hexaphenyl (6P) on sputter-modified mica, that under specific experimental conditions the nucleation has to be described by attachment limited aggregation (ALA). The crucial parameter for the growth mode is the roughness of the substrate surface, as induced by ion sputtering. With decreasing surface roughness the diffusion probability of the molecules increases and the growth mode changes from DLA to ALA. This was derived from the deposition rate dependence of the island density. A critical size of i = 7 molecules was determined for the nucleation of 6P on a moderately sputtered mica surface.